Direct C2‐Functionalization of Indoles Triggered by the Generation of Iminium Species from Indole and Sulfonium Salt. Issue 45 (20th July 2017) - Tayu, Masanori; Nomura, Kazuya; Kawachi, Koki; Higuchi, Kazuhiro; Saito, Nozomi; Kawasaki, Tomomi
Abstract: An indole core bearing a functional group on the C2 position is often found as a key structure in biologically active natural products and pharmaceuticals. Here, we report direct C2‐functionalization of indoles triggered by the formation of an iminium species generated from indole and a sulfonium reagent. The reaction proceeded under very mild conditions to give the corresponding C2‐substituted indole derivatives in good to high yields. Abstract : Pulling the trigger : Direct C2‐functionalization of indoles triggered by the formation of an iminium species generated from indole and a sulfonium salt is demonstrated. The reaction proceeded under very mild conditions to give the C2‐substituted indole derivatives in good to high yields.